Book Reviews (Rev. Anal. Numér. Théor. Approx., 1998)
Book reviews for:General Inequalities 7, Edited by C. BANDLE, W.N. EVERITT, L. LOSONCZI and W. WALTER, ISNM, vol.123, Birkhauser Verlag, Basel-Boston-Berlin 1997, 604 pp., ISBN 3-7643-5722-3. Reviewed by I. Rasa.MIKHAIL I. KADETS, VLADIMIR M. KADETS, Series in Banach Spaces. Conditional and unconditional convergence, Operator Theory, Advances and applications, Vol. 94, Birkhauser Verlag, Basel-Boston-Berlin,1997. Reviewed by I. Serb.I.V. NOVOZHILOV, Fractional Analysis, Methods of Motion Decomposition, Birkhauser Verlag, 1997, hardcover, 232 pp., ISBN 0-8176-3889-X. Reviewed by C. Blaga.LECH MALIGRANDA, Orlicz Spaces and Interpolation, Seminarios de Matematica, vol. 5, Univ. de Campinas (UNICAMP), Brasil, 1989, 206 pp. Reviewed by S. Cobzas.Multivariate Approximation and Splines, edited by: GUNTHER NURNBERGER, JOCHEN W. SCHMIDT and GUIDO WALZ, ISNM, vol. 125, Birkhauser Verlag, Basel-Boston-Berlin, 1997, 336 pp. Reviewed by Gh. Micula.HANS TRIEBEL, Fractals and Spectra-Related to Fourier Analysis and Function Spaces, Monographs in Math., vol. 91, Birkhauser Verlag, Basel-Boston-Berlin, 1997, hardcover, vii + 272 pp., ISBN 3-7643-5776-2. Reviewed by J. Kolumban.C.E. D'ATTELLIS, E.M. FERNANDEZ-BERDAGUER (Eds), Wavelet Theory and Harmonic Analysis in Applied Sciences, Applied and Numerical Harmonic Analysis, Series Editor: JOHN J. BENEDETTO, Birkhauser Verlag, Boston-Basel-Berlin, 1997, xviii + 346 pp., ISBN 0-8176-3953-5, 3-7643-3953-5. Reviewed by P. Blaga.